2000
DOI: 10.1063/1.1311953
|View full text |Cite
|
Sign up to set email alerts
|

Semiconducting boron carbonitride nanostructures: Nanotubes and nanofibers

Abstract: Highly oriented boron carbonitride (BCN) nanostructures consisting of nanotubes and nanofibers have been synthesized by bias-assisted hot-filament chemical vapor deposition from the source gases of B2H6, CH4, N2, and H2. It is found that the B concentration of the BCN nanostructures increases with increasing B2H6 in the gas mixture, and the highest B concentration is 45 at. %. Photoluminescence spectrum shows that the BCN nanostructures, identified as B0.34C0.42N0.24, are semiconductors with a band gap energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 14 publications
1
46
1
Order By: Relevance
“…3 It also opens a series of basic scientific questions regarding, e.g., charge transfer between B and C atoms, band-structure change, and charge-carrier localization. Recent studies [4][5][6][7] were mainly focused on boron and nitrogen doping of multiwalled carbon nanotubes (MWCNT). They have already successfully achieved boron or nitrogen incorporation by different procedures.…”
Section: Introductionmentioning
confidence: 99%
“…3 It also opens a series of basic scientific questions regarding, e.g., charge transfer between B and C atoms, band-structure change, and charge-carrier localization. Recent studies [4][5][6][7] were mainly focused on boron and nitrogen doping of multiwalled carbon nanotubes (MWCNT). They have already successfully achieved boron or nitrogen incorporation by different procedures.…”
Section: Introductionmentioning
confidence: 99%
“…The 1355 and 1572 cm -1 peaks correspond to the D and G bands of B-C-N compounds, respectively-this result agrees with those obtained in the study on B-C-N nanotubes. [18][19][20] Another confirmation of the disappearance of h-BN is the more obvious 1355 cm -1 peak in the spectroscopic characterization of the deposits on the cathode. The second-order Raman spectra at the range of high Raman shift can be assigned to a combination of D and G bands of graphite-like structures, [21,22] such as the 2592 cm -1 peak, in agreement with results obtained by X-ray diffraction and transmission electron microscopy.…”
mentioning
confidence: 88%
“…Since the discovery of B X C Y N Z nanotubes in 1994 44 , several experimental [45][46][47][48][49][50][51][52][53][54][55][56][57] and theoretical [58][59][60][61][62][63][64][65][66] works have been done to understand of the properties of this new material. Theoretical studies have revealed that the electronic properties of B X C Y N Z nanotubes are unrestricted by geometrical structure and can be controlled by simply varying the chemical composition 61,67,68 .…”
Section: Structural Properties and Enthalpy Of Formationmentioning
confidence: 99%